2017
DOI: 10.1016/j.sjbs.2017.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Combined efficacy of Vigna radiata (L.) R. Wilczek and Amorphophallus paeoniifolius (Dennst.) Nicolson on serum lipids in albino rats

Abstract: Coronary Artery Disease (CAD) is a major killer disease throughout the world. Dyslipidemia is a major contributor to the risk of CAD. Several dietary articles traditionally used in India and other South Asian countries reduced dyslipidemia. The present study was undertaken to evaluate the combined effect of Mung bean () and Elephant foot yam () on serum lipids and atherogenic indices in albino rats and to compare it with a standard drug Cholestyramine. Thirty healthy albino rats of both sexes (150-200 g) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…of this mixture was administered to albino mice models, which was caused by lowering the hormone leptin levels. The hypolipidemic activity of A. paeoniifolius glucomannan was comparable to that of statins, involving the competitive inhibition of HMG-CoA reductase and reduced LDL production [96]. In another study, Safitri et al [97] demonstrated that Porang glucomannan administered at doses between 25 and 100 mg/200 g b.w.…”
Section: Reduction Of Blood Glucosementioning
confidence: 97%
“…of this mixture was administered to albino mice models, which was caused by lowering the hormone leptin levels. The hypolipidemic activity of A. paeoniifolius glucomannan was comparable to that of statins, involving the competitive inhibition of HMG-CoA reductase and reduced LDL production [96]. In another study, Safitri et al [97] demonstrated that Porang glucomannan administered at doses between 25 and 100 mg/200 g b.w.…”
Section: Reduction Of Blood Glucosementioning
confidence: 97%
“…The combination of powdered sprouted mung bean (green gram ) and yam powder (Amorphophallus paeoniifolius) have significantly reduced the serum lipid levels as well as the atherogenic indices in albino rats in comparison to the, bile acid sequestering agent, Cholestyramine as standard. Thus use of this combination could help in reducing high CAD risk among Asians [22].…”
Section: Number Of Documents Publishedmentioning
confidence: 99%